Traumatismos maxilofaciais como marcadores de violência urbana em Belo Horizonte-MG: uma análise epidemiológica e socioespacial - Carlos Jose de Paula Silva (2013)
Urban violence in Brazil has become a public health issue. It is present in the daily life of brazilian people, producing a large number of victims, physical and emotional consequences. The maxillofacial injury is a type of trauma that occurred in the face and head. The number of maxillofacial injuries may be associated with the exposure of this region of the body in cases of traffic accidents or an attempt to disfigure the face of the victims of aggression. This study analyzed the maxillofacial injuries while markers of urban violence and characterize them according to gender, age groups, types of violence, days and times of occurrence and sought to understand the spatial pattern of cases by associating them with social conditions and infrastructure of the place of residence. This is a cross-sectional study with data collected in three hospitals of reference for this kind of injuries in Belo Horizonte, Brazil. Were Included the cases registered between January 2008 and December 2010. The analyzis included descriptive statistics, logistic regression and spatial analyzis. The spatial analysis involved multicriteria analysis, Ripley´s K function, K 12 function and maps of Kernel. Were identified records of 7.063 victims of maxillofacial injuries, of which 55.1 % were due to interpersonal violence and 44.9 % motor vehicle accidents. Most of the victims (71.2 %) were male, with an average age of 29.6 years (±13.8; 1-92) and the greater part had 30 to 50 years of age. Among men the cases of interpersonal violence accounted for 40 %.There was a predominance of physical aggression (47.85 %) and the greater part of injuries was characterized by lesions in the soft tissues (43.21 %). In male victims aggressions with gunshoting, stabing of knife and motorcycle crashes were more frequent them aggression without use of a weapon (slaps, punches and kicks). The multiple fractures were the type of injuries that best characterized the profile of victimization for males compared to soft tissue injuries (p<0.001; OR 2.78; IC 95 %; 2.31; 3.36). The cases of violence were concentrated during the evening (59.52 %) and between monday and friday (60.07 %). Statistically significant association was found between the male (p=0.016; OR 1.24; IC 95%; 1.04; 1.48), firearm aggression (p<0.001; OR 4.18; IC 95%; 2.74; 6.40), motorcycle accidents (p=0.001; OR 3.23; IC 95%; 1.16; 1.81) and the need for surgical approach of cases. Of total of 5.012 victims living in Belo Horizonte-MG. These cases were geo-referenced and presented a aggregate patterns in territory a confidence level of 99 %. The high densities of cases were recorded in regions characterized by areas of great socio-economic disparity. Were identified regions with high density of victims associated with regions with significant spatial vulnerability characteristics according to socioeconomic conditions, infrastructure of residence and neighborhood.